Enhancing Transformation: The Value of Applying Narrative Therapy Techniques When Engaging in Critical Reflection. (October 2019) - Edwards, Thomas Mark; Walker, Michael
Transformative learning (TL) is a powerful approach to education. Instead of promoting the efficient encoding and recall of information, TL has students identify, and consider, the assumptions they hold about their discipline and the wider world. Although disorientating dilemmas are the hallmark of TL, personal change cannot happen without subsequent critical reflection. For this reason, critical reflection represents the central mechanism of transformation. The current article identifies synergies between TL and narrative therapy (NT) valuable for the enhancement of critical reflection. In particular, the advantages of NT techniques such as externalisation, outsider witness, and identifying the absent but implicit within a story are discussed. By integrating NT practices within critical reflection it is hoped that a greater degree of transformation will result for students.